2001
DOI: 10.1080/09629350120102361
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of serum soluble E‐selectin and VCAM‐1 in severe asthma

Abstract: Objective: To investigate the significance of circulating adhesion molecules associated with leucocyteendothelial cell interactions in asthma, serum levels of soluble E (sE)-selectin, soluble P (sP)-selectin, soluble L (sL)-selectin, and soluble vascular cell adhesion molecule-1 (sVCAM-1) were measured in mild, moderate and severe asthma. Method: Serum levels of sE-selectin, sP-selectin, sLselectin, and sVCAM-1 were measured in 32 women with asthma and 30 healthy donors using an enzymelinked immunosorbent assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
1
10
1
Order By: Relevance
“…We have confirmed similarities in baseline serum levels of P-selectin in asymptomatic patients with mild asthma and in volunteers, findings which are in agreement with results from a recent study [16]. We have now also shown that repeated inhalations of salbutamol lowered P-selectin levels, and in agreement with well-known drug effects, also improved lung function in the asthmatics.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We have confirmed similarities in baseline serum levels of P-selectin in asymptomatic patients with mild asthma and in volunteers, findings which are in agreement with results from a recent study [16]. We have now also shown that repeated inhalations of salbutamol lowered P-selectin levels, and in agreement with well-known drug effects, also improved lung function in the asthmatics.…”
Section: Discussionsupporting
confidence: 81%
“…Short-acting β-2 agonists can, in vitro, inhibit expression of CAMs such as CD11b and L-selectin, and also inhibit the production of leukotrienes and eosinophil peroxides [16]. A similar decrease in serum markers in subjects with no asthmatic inflammation would theoretically speak against the decrease being solely a result of an anti-inflammatory effect of salbutamol.…”
Section: Discussionmentioning
confidence: 99%
“…sVCAM-1 binds with α4β1 integrins and alters lymphocyte functions and angiogenesis (48,49). sVCAM-1 levels are elevated in biological fluids in various diseases, including synovial fluids from patients with rheumatoid arthritis (50), cerebrospinal fluid from patients with active multiple sclerosis (51) and alveolar lining fluid from patients with eosinophilic pneumonia and asthma (52). However, the physiological functions of sVCAM-1 are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple lines of evidence have shown the production of sVCAM‐1 in the circulation and inflammatory sites of asthmatics. The plasma level of sVCAM‐1 in asthmatic patients (753 ± 60.8 ng/ml) is higher than that of healthy controls (580 ± 70.7 ng/ml) (10). Koizumi et al.…”
Section: Discussionmentioning
confidence: 99%
“…Adhesion molecules, including VCAM‐1, undergo proteolytic cleavage, which releases the soluble ectodomain from the cell surface. Soluble forms of adhesion molecules are increased in the sputum (9), serum (10, 11), and bronchoalveolar lavage fluid (BALF) (12) of asthmatic patients. Elevated levels of soluble adhesion molecules reflect the activity of asthma; therefore, these molecules can be useful inflammatory markers (10, 11).…”
mentioning
confidence: 99%